Thái độ và kì vọng của sinh viên sư phạm tiếng Anh đối với ChatGPT: nghiên cứu tại Trường Đại học Sư phạm Hà Nội - Thái , Thị Cẩm Trang (Tạp chí Giáo dục, 2023)
ChatGPT is an artificial intelligence tool with potential applications in foreign language learning to support the current learning as well as the teaching career of future teachers. The study used convergent mixed-methods design, collected data through surveys and interviews with English pedagogical students at Hanoi National University of Education in order to assess the familiarity and application of ChatGPT as well as the attitude of EFL pre-service teachers towards its potential to support future learning and teaching. The results showed that most of the students participating in the study had heard of ChatGPT and some used it for learning purposes. The participants showed a positive attitude towards ChatGPT’s ability to support learning, giving examples of its ability to provide quick and accurate answers and its potential to improve language skills. However, they also expressed concerns about the reliability and accuracy of the information provided by ChatGPT and the negative effects on critical thinking skills. The study leads to suggestions for the integration of ChatGPT and other artificial intelligence tools in English language teaching and proposes further research to explore its effectiveness and related ethical issues.